Rescue Allocation Modes in Eurotransplant Kidney Transplantation: Recipient Oriented Extended Allocation Versus Competitive Rescue Allocation - A Retrospective Multicenter Outcome Analysis - Assfalg, Volker; Miller, Gregor; Stocker, Felix; Hüser, Norbert; Hartmann, Daniel; Heemann, Uwe; Tieken, Ineke; Zanen, Wouter; Vogelaar, Serge; Rosenkranz, Alexander R.; Schneeberger, Stefan; Függer, Reinhold; et al. (Transplantation, 2024)
Background. Whenever the kidney standard allocation (SA) algorithms according to the Eurotransplant (ET) Kidney Allocation System or the Eurotransplant Senior Program fail, rescue allocation (RA) is initiated. There are 2 procedurally different modes of RA: recipient oriented extended allocation (REAL) and competitive rescue allocation (CRA). The objective of this study was to evaluate the association of patient survival and graft failure with RA mode and whether or not it varied across the different ET countries. Methods. The ET database was retrospectively analyzed for donor and recipient clinical and demographic characteristics in association with graft outcomes of deceased donor renal transplantation (DDRT) across all ET countries and centers from 2014 to 2021 using Cox proportional hazards methods. Results. Seventeen thousand six hundred seventy-nine renal transplantations were included (SA 15 658 [89%], REAL 860 [4.9%], and CRA 1161 [6.6%]). In CRA, donors were older, cold ischemia times were longer, and HLA matches were worse in comparison with REAL and especially SA. Multivariable analyses showed comparable graft and recipient survival between SA and REAL; however, CRA was associated with shorter graft survival. Germany performed 76% of all DDRTs after REAL and CRA and the latter mode reduced waiting times by up to 2.9 y. Conclusions. REAL and CRA are used differently in the ET countries according to national donor rates. Both RA schemes optimize graft utilization, lead to acceptable outcomes, and help to stabilize national DDRT programs, especially in Germany.
CRIS-Team Scopus Importer:2024-05-10